Experimental evolution reveals natural selection on standing genetic variation - Teotónio, H (2010)
Evolution depends on genetic variation generated by mutation or recombination from standing genetic variation. In sexual organisms, little is known about the molecular population genetics of adaptation and reverse evolution(1-11). We carry out 50 generations of experimental reverse evolution in populations of Drosophila melanogaster, previously differentiated by forward evolution, and follow changes in the frequency of SNPs in both arms of the third chromosome. We characterize the effects of sampling finite population sizes and natural selection at the genotype level. We demonstrate that selection has occurred at several loci and further that there is no general loss or gain of allele diversity. We also observe that despite the complete convergence to ancestral levels of adaptation, allele frequencies only show partial return.